Stock market reaction to the military conflict between Russia and Ukraine: An event study for the European tourism and hospitality industry - António Miguel Martins; Pedro Álvaro Pereira Correia; Susana Cró (Journal of Applied Economics, 2023)
This paper examines the short-term market reaction of European tourism and hospitality industry to the beginning of the military conflict between Russia and Ukraine (24 February 2022). Using an event study, for a sample of 165 listed firms, we observe a negative and statistically significant stock price reaction at and around the beginning of the military conflict between Russia and Ukraine. These results are consistent with investor sentiment hypothesis and asset-pricing perspective. These reactions are reinforced or mitigated by firm-specific characteristics such as liquidity, size, profitability, and institutional ownership. Finally, we find that listed firms located in: (i) countries in which Russia and Ukraine are the largest source of inbound foreign tourists, and (ii) countries formerly occupied by the Soviet Union and/or that share a common border with Russia, tend to show more negative abnormal returns.
Keywords: 330; event study; stock returns; tourism; War